KETERAMPILAN MENULIS PARAGRAF DESKRIPTIF BAHASA JERMAN DENGAN METODE ESTAFET WRITING BERMEDIA GAMBAR SISWA KELAS X SMAN 1 GEDANGAN - KATHARINA MOI S., ROSINA (LATERNE, 2018)
Writing is one of the productive aspects that produces a language. Writing skills should be trained regularly so, can produce a good and correct writing. In the process of German learning, not all students are able to write good and correctly. Particularly in writing German essay, students often have difficulty writing a sentence. For that we need an effective method and effective strategy that is Estafet Writing method using picture media. The application of the Estafet writing method and using picture media as a supporter can involve all students to share their knowledge and ideas and then develop their imagination through a written. The formulation of this research problem is: how the process of applying the method of Estafet Writing using picture media in writing skill learning of German language class X SMAN 1 Gedangan ?. The purpose of this research is to describe the process of applying the Estafet writing method using picture media in writing skills learning German opus writing student class X.      This type of this research is a qualitative research. Data collection techniques use observation sheets (observation), documentation and tests to support the process of applying the method of Estafet Writing using picture media. The study was conducted on March 24 - 7 April 2017, three times meeting and followed by 34 students.             Based on the result of the research, it can be concluded that the method of Estafet Writing using picture media is effective applied in learning the writing skill of German language paragraph. This can be seen from the successful implementation of the method of Estafet Writing using picture media shown through observation data. In addition, the more attention of students of SMAN 1 Gedangan with the method of Estafet Writing using picture media.                                                            Keywords       : Estafet Writing method, Writingskills